Techniques and methods of translation in short story Is That So? I’m A Giraffe by Min-gyu Park - Karina Sita Putri; Velayeti Nurfitriana Ansas; Didi Sukiyadi (Journal of Korean Applied Linguistics, 2022)
The same is true of the Indonesian translation of a Korean short story. Undoubtedly, the process is not simple. This study aims to find out the use of translation techniques, the use of translation methods, and the application of translation techniques and methods used in equivalents of the short story Is That So? I’m a Giraffe by Min-Gyu Park and using Molina and Albir's theory of translation techniques, Newmark's theory of translation method, and Nida and Taber's equivalence theory. This study used a descriptive qualitative method by analyzing the words, phrases, clauses, and sentences contained in the short story as the data source. The note-taking technique was also used. The results of the data analysis showed that there were ten translation techniques and eight translation methods used in translating the text. The modulation technique was the most frequently used technique with 172 occurrences, and the free translation method was the most common method with 176 occurrences. Based on these results, the translation of the short story is included in the dynamic equivalence which is more concerned with the meaning of the target language.